2014
DOI: 10.1007/s00383-014-3595-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for mortality following acute pancreatitis in children

Abstract: Mortality rate and complication rate of acute pancreatitis in children remains low. Patients with SIRS, early organ failure, MOF, infected necrosis, or idiopathic cause should be well evaluated because they have higher risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…19,23,24 Mortality rate was found 5.7% in a group of children with AP that were hospitalized in pediatric intensive care unit. 25 Guo et al 26 found the mortality rate of 5% in children with AP, and patients with systemic inflammatory response syndrome in the first week of onset, early organ failure, and multiorgan failure in the first week of onset, infected necrosis, and idiopathic cause have higher risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…19,23,24 Mortality rate was found 5.7% in a group of children with AP that were hospitalized in pediatric intensive care unit. 25 Guo et al 26 found the mortality rate of 5% in children with AP, and patients with systemic inflammatory response syndrome in the first week of onset, early organ failure, and multiorgan failure in the first week of onset, infected necrosis, and idiopathic cause have higher risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of acute pancreatitis (AP) in the pediatric population has increased in the last 2 decades (1), ranging from 3.6 to 13.2 cases per 100,000 children (2,3), with a mortality rate between 4% and 10% (4,5).…”
mentioning
confidence: 99%
“…Multiple symptoms may present starting from an early age, including episodic abdominal pain, eruptive cutaneous xanthomata, and hepatosplenomegaly (Feoli-Fonseca et al, 1998). The most severe and life-threatening complication of FCS is acute pancreatitis, which is shown to have a mortality rate of 5-30% in multiple studies (Guo et al, 2014;Gaudet et al, 2016). FCS shows a classic autosomal recessive inheritance pattern, and the prevalence in the United States population is approximately 1 in 1,000,000 (Hegele et al, 2014).…”
Section: Introductionmentioning
confidence: 99%